2017
DOI: 10.3390/ijerph14040382
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Health Risk Assessment of Electronic Cigarettes and Conventional Cigarettes

Abstract: Background: Although some studies have identified hazardous substances in electronic cigarette (EC) liquids and emissions, there is limited information about the health risks of using ECs. Methods: In this study, the U.S. Environmental Protection Agency (EPA) health risk assessment model and findings of a literature review were used to determine and profile hazards. Focus was put on the toxicants reported in the literature on conventional cigarette (CC) smoke that most strongly associated with adverse health e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 7 publications
0
36
0
1
Order By: Relevance
“…A 2016 report by the WHO stated that there is not enough research to quantify the relative risk of NVPs over combustible products , and WHO has previously urged countries to restrict the sale, promotion and use of electronic cigarettes . Additionally, some recent reviews have also demonstrated the inconclusive evidence about the health risks associated with NVPs use . Therefore, our data may be indicating that HPs in England (and in the other countries) may be conflicted about the role of NVPs in smoking cessation due to the opposing positions of various NGO and public health organizations.…”
Section: Discussionmentioning
confidence: 78%
“…A 2016 report by the WHO stated that there is not enough research to quantify the relative risk of NVPs over combustible products , and WHO has previously urged countries to restrict the sale, promotion and use of electronic cigarettes . Additionally, some recent reviews have also demonstrated the inconclusive evidence about the health risks associated with NVPs use . Therefore, our data may be indicating that HPs in England (and in the other countries) may be conflicted about the role of NVPs in smoking cessation due to the opposing positions of various NGO and public health organizations.…”
Section: Discussionmentioning
confidence: 78%
“…Flavours increase product attractiveness among all types of (potential) users, that is, among youth and adults8 and among current smokers, dual users, exclusive vapers, as well as never-users 9. For smokers, switching to e-cigarettes may be beneficial, as e-cigarette use (ie, vaping) is considered less harmful than regular cigarette smoking 10–14. In line with this, the use and marketing of e-liquid flavours that are appealing to smokers may contribute to public health benefits.…”
Section: Introductionmentioning
confidence: 98%
“…This study points to challenges and avenues for future research about e-cigarette warnings. E-cigarettes pose the potential for nicotine addiction and accidental exposure, and may also expose users to some chemicals and carcinogens [ 8 , 9 , 10 ]. However, the science on potential e-cigarette health effects is nascent and research thus far suggests that they appear to be much less harmful to individual health than tobacco cigarettes [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…E-cigarettes are novel products that appear to be much less harmful to individual health than tobacco cigarettes [ 6 , 7 ], but are not completely harmless [ 8 ]. They pose potential for nicotine addiction and accidental exposure, and may also expose users to some chemicals and carcinogens (although much less so than cigarette smoking) [ 8 , 9 , 10 ]. Thus, consideration of warnings for e-cigarettes appears relevant.…”
Section: Introductionmentioning
confidence: 99%